2021
DOI: 10.1093/hmg/ddab107
|View full text |Cite
|
Sign up to set email alerts
|

RNA kinase CLP1/Cbc regulates meiosis initiation in spermatogenesis

Abstract: CLP1, TSEN complex, and VCP are evolutionarily conserved proteins whose mutations are associated with neurodegenerative diseases. In this study, we have found that they are also involved in germline differentiation. To optimize both quantity and quality in gametes production, germ cells expand themselves through limited mitotic cycles prior to meiosis. Stemming from our previous findings on the correlation between mRNA 3′-processing and meiosis entry, here we identify that the RNA kinase Cbc, the Drosophila me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Although previous studies have demonstrated that VCP influences germ-cell health and development (León and McKearin, 1999; Sasagawa, et al, 2012; Sasagawa, et al, 2009; Sasagawa, et al, 2007; Wu, et al, 2021), fundamental questions remain regarding how VCP functions and is regulated in this biological context, particularly in the male germline. In this study, we found that VCP translocates from the cytosol to the nucleus at the mitotic-meiotic transition, and downregulates H2Aub to promote changes in gene expression needed for subsequent stages of spermatogenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have demonstrated that VCP influences germ-cell health and development (León and McKearin, 1999; Sasagawa, et al, 2012; Sasagawa, et al, 2009; Sasagawa, et al, 2007; Wu, et al, 2021), fundamental questions remain regarding how VCP functions and is regulated in this biological context, particularly in the male germline. In this study, we found that VCP translocates from the cytosol to the nucleus at the mitotic-meiotic transition, and downregulates H2Aub to promote changes in gene expression needed for subsequent stages of spermatogenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In oocytes of the nematode Caenorhabditis elegans , CDC-48/VCP appears particularly significant during meiotic divisions, when it regulates chromosome condensation and segregation (Mouysset, et al, 2008; Sasagawa, et al, 2012; Sasagawa, et al, 2009; Sasagawa, et al, 2007). While there are indications that VCP may likewise perform regulatory roles during sperm development (Wu, et al, 2021), it is unclear at what stage VCP function may be most critical. Stage-specific transcriptomic data from Drosophila testes suggest that ter94/VCP is strongly expressed in meiotic-stage spermatocytes (Shi, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further increase KD penetrance, we used a Gal4 driver that also expressed UAS > dicer2. Fly lines used in this study: W1118 (BL #3605), Bam Gal4 (Chen and McKearin 2003), CPSF6:GFP (VDRC #318105), HA:Cbc (N-terminal CRISPR tag, kindly gimed from the Wang lab, (Wu et al 2021)), PCF11-RNAi_1…”
Section: Fly Strains and Husbandrymentioning
confidence: 99%
“…The homolog of CLP1 (cbc) in Drosophila has been demonstrated to be necessary for spermatogenesis and function of this gene can be recovered in KO flies using human and mouse orthologs, suggesting a similar function (Wu et al, 2021).…”
Section: M1ap (Meiosis-1 Associated Proteinmentioning
confidence: 99%